Vocational training for rural populations: A demand-driven approach and its implications in India - Muthuveeran Ramasamy; Matthias Pilz (International Journal for Research in Vocational Education and Training (IJRVET), 2020)
Context: Vocational training is viewed as a significant tool that increases employment outcomes and provides potential career advancement opportunities for individuals. Many countries are witnessing a shift from supply-driven to demand-driven approaches. The demand-driven approach in vocational training is often explored at the macro level and is associated with the perspectives of employers and labour markets. In contrast, this article explores the demand-driven approach at the micro level by focusing on the perspectives of individual learners within the context of their localities in order to position them at the centre of the skill development process. Methods: This study used a qualitative exploratory research method and a mixture of focus group and face-to-face semi-structured interviews to obtain data to identify the practical problems that arise in real life contexts when attempts are made to prioritise vocational training demands in line with the needs of all the stakeholders. Based on the demand from the targeted learners, a competency-based vocational training course especially for women was designed, tested and evaluated in selected villages. Findings: The results show clearly that the demands of the rural population varied, and their participation in the training course was highly influenced by access to a training centre, the duration of the training, economic returns and socio-cultural factors. The demand-driven approach works best in vocational training when it involves the relevant stakeholders and the target groups in the planning and designing process. Conclusion: The findings illustrate that demand-driven approach should be context specific, responsive to individuals'/learners' demands, relevant and flexible.
Keywords: 330; VET; Vocational Education and Training; Vocational Training; Demand-Driven Approach; India; Needs Assessment; Women